Advances in bionergy (John Wiley & Sons, 2016)
This book will be a vital reference to engineers, researchers and students that need an accessible overview of the bioenergy area. It will also be of high value for politicians, policymakers and industry leaders that need to stay up to date with the state-of-the-art science and technology in this area.